Attitudes of Graduate Students in Speech and Language Therapy toward Individuals with Special Needs - Uysal, Halil Tayyip; Kirazli, Meltem Cigdem; Miraloglu, Kubra; Kose, Aysen (Journal of Qualitative Research in Education, 2025)
Understanding the attitudes of healthcare professionals and students is crucial for enhancing the quality and accessibility of services provided to individuals with special needs (IWSN). Speech and Language Therapy (SLT) professionals play a central role in the multidisciplinary support of these individuals, making it essential to explore the perspectives of future practitioners. This study investigates the attitudes of graduate SLT students toward IWSN, with the goal of informing educational practices and contributing to professional development. A qualitative research design was adopted, involving semi-structured interviews with 8 graduate-level SLT students enrolled in master’s and doctoral programs. Thematic analysis was conducted using MAXQDA software to identify patterns and insights within the data. The findings revealed that participants generally held positive attitudes toward IWSN, regardless of their level of study. Four overarching themes emerged from the analysis: (a) family relations, (b) academic, social, and public issues, (c) emotional responses of graduate students, and (d) perceived professional needs. Although some students initially expressed hesitation, they reported a shift in attitudes over time, attributing this change largely to experiential learning opportunities. The study highlights the importance of integrating real-life experiences into SLT training programs and promoting broader awareness among students, families, and the wider community to enhance support for IWSN.